SCIENTIFIC COOPERATION ACROSS THE BRICS - M. Astakhova (BRICS Law Journal)
The creation of the BRICS as a non-traditional international organization in the status of a global forum brings new meaning to the norm-setting of international organizations, including in the field of scientific cooperation. This paper aims to identify and analyze the up-to-date and complete normative framework of scientific cooperation across the BRICS which is a result of the BRICS norm-setting. The achievement of the stated aim is pursued through the identification of the distinctive features of the BRICS norm-setting by comparison with the norm-setting of traditional international intergovernmental organizations and by analysis of the BRICS regulations dealing with issues of scientific cooperation. Within the process of researching this subject the author analyzed the BRICS regulations of different levels from the Joint Statements of the BRICS Countries’ Leaders and the Summits Declarations to the BRICS working papers as aframework program. The main finding of the research is that the normative framework of scientific cooperation across the BRICS is a set of non-legally binding norms contained in the regulations adopted at the various meetings of national officials within the BRICS. This finding can contribute to a better understanding of the application of the BRICS norms.